Influence of mental image and creativity in the artistic process through strategies of unpredictability - María José Pérez-Fabello; Thomas Apostolou (Revista de Estudios e Investigación en Psicología y Educación)
This study focused on the field of imagination and creativity in the classroom by proposing a creative learning experience to a group of 92 fine arts students. Following a theoretical reflection on strategies of unpredictability in artistic creation, participants were asked to develop an artistic project in which chance intervened at some point in the creative process. Our objective was to evaluate the influence of image control, creative thinking, and creative experiences on the realization of an artistic project. Two expert judges measured the originality, the elaboration, and the total score of each project. The results demonstrated the importance of mental imagery and creative thinking in artistic creation. Image control and creative thinking influenced the originality of the project. It can be interesting to develop creative learning experiences that involve imagination and creative thinking in the classroom. In addition, future research work is proposed.